Pengaruh Inflasi dan Suku Bunga Terhadap Indeks Harga Saham Gabungan - Koapaha, Hartini Pop (JBE (Journal of Business and Economics), 2012)
The aim of this research is to analyze the impact of macroeconomics factors ( inflation and BI rate) to the Indeks Harga Saham Gabungan (IHSG).  Therefore, this research has constructed three research questions and three hypotheses. The method used in this research are simple linear regression model to analyze the impact of the inflation and BI rate to the price index of IHSG.   The result of this research show that the inflation and does not affect IHSG partially. However BI rate has a significant influence toward IHSG.